Doping of ultra-thin Si films: Combined first-principles calculations and experimental study - Gity, Farzan; Meaney, Fintan; Curran, Anya; Hurley, Paul K.; Fahy, Stephen; Duffy, Ray; Ansari, Lida (Journal of applied physics, 2021)
This paper presents comprehensive density functional theory-based simulations to understand the characteristics of dopant atoms in the core and on the surface of ultra-thin sub-5 nm Si films. Quantum confinement-induced bandgap widening has been investigated for doped Si films considering two different doping concentrations. Thickness-dependent evolution of dopant formation energy is also extracted for the thin films. It is evident from the results that doping thinner films is more difficult and that dopant location at the surface is energetically more favorable compared to core dopants. However, the core dopant generates a higher density of states than the surface dopant. Projecting the carrier states in the doped Si film onto those of a reference intrinsic film reveals dopant-induced states above the conduction band edge, as well as perturbations of the intrinsic film states. Furthermore, to experimentally evaluate the ab initio predictions, we have produced ex situ phosphorus-doped ultra-thin-Si-on-oxide with a thickness of 4.5 nm by the beam-line ion implantation technique. High-resolution transmission electron microscopy has confirmed the thickness of the Si film on oxide. Transfer length method test structures are fabricated, and the temperature-dependent electrical characterization has revealed the effective dopant activation energy of the ion-implanted phosphorus dopant to be ≤ 13.5 meV, which is consistent with our theoretical predictions for comparable film thickness. Ultra-thin Si films are essential in the next generation of Si-based electronic devices, and this study paves the way toward achieving that technology.